Wdrożenie i eksploatacja sklepu internetowego schemat aplikacyjny - Moroz, Mirosław (The Pattern of Implementation and Operation of an Electronic Store, 2005)
The article proposes a pattern of implementation and operation an electronic store. There's no doubt that establish and run the Internet store is risky business in term of changeability of the virtual space. The presented scheme organizes all activities and measures into five stages: defining conception and plan, making a decision regarding the localization of a server and a kind of the electronic store, defining Web Usability, promotion of the store and on-going operations as a final stage. From a practical perspective, this paper has demonstrated the pattern that is useful for enterprises which are going to establish and then develop of a successful electronic store.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 183-192